2020
DOI: 10.1097/md.0000000000021132
|View full text |Cite
|
Sign up to set email alerts
|

Increased repeat syphilis among HIV-infected patients

Abstract: Among human immunodeficiency virus (HIV)–infected individuals, syphilis is an important sexually transmitted infection (STI), and repeat infections are common. Identifying risk factors for delineating the trends in repeat syphilis are essential for STI and HIV prevention. This study is to investigate the dynamic of the syphilis epidemic among HIV-infected patients and to identify the risk factors associated with repeat syphilis. A population-based cohort design was used to analyze claim d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…It is encouraging that the reported prevalence of syphilis in this study is similar to the prevalence of syphilis among PLHIV reported in Ethiopia [ 23 ]. Although the prevalence of syphilis in our study may have been overestimated due to the limitations of the test kits in reacting to non-treponemal infections, studies in other African countries such as Nigeria (14.0%), Ghana (14.8%), Morocco (16.4%), Chad (14.0%), and Tanzania (9.6%) reported a higher prevalence [ 8 10 , 24 26 ]. The disparities in these findings may be due to the different composition of the study populations and differences in the methods applied for the detection of syphilis or perhaps may reflect the variations in the risky behavioral practices across the African region.…”
Section: Discussionmentioning
confidence: 60%
“…It is encouraging that the reported prevalence of syphilis in this study is similar to the prevalence of syphilis among PLHIV reported in Ethiopia [ 23 ]. Although the prevalence of syphilis in our study may have been overestimated due to the limitations of the test kits in reacting to non-treponemal infections, studies in other African countries such as Nigeria (14.0%), Ghana (14.8%), Morocco (16.4%), Chad (14.0%), and Tanzania (9.6%) reported a higher prevalence [ 8 10 , 24 26 ]. The disparities in these findings may be due to the different composition of the study populations and differences in the methods applied for the detection of syphilis or perhaps may reflect the variations in the risky behavioral practices across the African region.…”
Section: Discussionmentioning
confidence: 60%
“…Outro resultado importante foi a maior ocorrência de sífilis em homens. E isso é mencionado em outros estudos especificamente entre os homens que fazem sexo com outros homens (HSH) (Lee et al, 2020) 16 . É importante conhecer os fatores relevantes para as diferentes populações, não só em termos de faixa etária e orientação sexual, mas também conhecer os cenários em que vivem, para propor intervenções intersetoriais e, no setor saúde.…”
Section: Diagrama De Resultadosunclassified

Fatores associados à sífilis adquirida em pessoas idosas: uma revisão integrativa

Dhyanine Morais de Lima Raimundo,
Ana Beatriz Pereira da Silva,
Maria Eduarda Silva Nascimento
et al. 2023
RIAGE
“…The increased detection rate means that the syphilis epidemic is on the rise in the municipality. Several studies have emphasized the resurgence of syphilis in specific populations, including men who have sex with men (MSM), in various parts of the world 22,23 . Notified cases can be considered to be either prevalent or incident, since it is not always possible to identify the clinical stage of the disease 6 .…”
Section: Discussionmentioning
confidence: 99%